ESRA19-0562 Bilateral continuous erector spinae planeblocks for the management of post-thoracosternotomy pain in patients undergoing lung transplantation – initial experience at toronto general hospital. (30th August 2019) - Hanley, C; Ladak, S; Jiang, J; Tamir, D; Ansari, B
Abstract : Background and aims: The management of postoperative pain is a challenging and contentious issue in patients who undergo lung transplantation. Poorly managed acute pain may have a significant adverse impact on clinical outcomes. In particular, the impact on respiratory mechanics may lead to graft dysfunction and prolonged mechanical ventilation. Thoracic epidural analgesia (TEA), the gold standard, is frequently precluded. The erector spinae plane (ESP) block, a novel interfascial plane block, has been shown to provide efficacious analgesia in thoracic patients, whilst potentially avoiding the complications of TEA. Methods: We conducted a retrospective review of 15 patients who had bilateral ESP blocks placed intraoperatively for the management of pain following lung transplantation. We reviewed opioid consumption and pain scores in the first 72 hours, time to extubation, functional outcomes, and any documented technical block issues. Results: Fifteen patients underwent lung transplantation via bilateral thoracosternotomy. Thirteen required intraoperative VA-ECMO. There was a reduction in overall opioid use in the first 72 hours. Mean numerical pain scores were 4 at rest (range 2–6), and 6 with movement (range 2–10). The majority were extubated within the first 12–24 hours, commenced initial physiotherapy exercises on postoperative day (POD) 1, and were ambulatory on POD 2. Catheter dislodgement occurred in 3 patients. Patient satisfaction was excellent overall. Conclusions: The ESP block is a useful addition to our armamentarium in the management of acute pain following lung transplantation. To the best of our knowledge, this is the first case series describing the ESP block in this group.